Histopathological Study of Urinary Bladder Cancer in a Group of Iraqi Patients from 2019 to 2024 - Zhraa D. Salman; Ban J. Mohamad (مجلة كلية الطب)
Background: Urinary bladder cancer (UBC) is the most common urinary tract malignancy, ranking tenth worldwide. In Iraq, UBC is ranked as the seventh most prevalent cancer among the top 10 cancers. Numerous established risk factors for bladder cancer including genetic and hereditary factors, smoking and nicotine behaviors, occupational exposure to certain chemicals and pigments, and environmental pollution from drinking water contaminated with arsenic may also be problems, as well as disorders including chronic cystitis, and infectious diseases like schistosomiasis. Urine cytology and cystoscopy are the gold standard for detecting UBC.